The Abscopal Effect of Radiation Therapy: What Is It and How Can We Use It in Breast Cancer? - Hu, Zishuo I. (Curr Breast Cancer Rep, 2017)
The abscopal effect refers to the ability of localized radiation to trigger systemic antitumor effects. Over the past 50 years, reports on the abscopal effect arising from conventional radiation have been relatively rare. However, with the continued development and use of immunotherapy strategies incorporating radiotherapy with targeted immunomodulators and immune checkpoint blockade, the abscopal effect is becoming increasingly relevant in less immunogenic tumors such as breast cancer. Here, we review the mechanism of the abscopal effect, the current preclinical and clinical data, and the application of the abscopal effect in designing clinical trials of immunotherapy combined with radiotherapy in breast cancer.